(untitled) (Global Journal of Science Frontier Research, 2017)
This paper endeavors to explain the Universe creation stages and aims to complement the model proposed in ‘A Single System Universe: A Cognitive Approach’ adopting the same cognitive approach. The stages are the initial precompression era from the infinite realm, compression era, and the finite Universe era. The explanation is a function of the matter/energy interaction modes. Matter changed in the three processes from particles with an essence of mass into ‘massable’ particles of Dark Matter. Energy transformed from crude into functional energy, referred to as Dark Energy, responsible for matter integration and universal expansion. Matter and Energy are different in essence and non reciprocal. Finally, the paper calls for empirical evaluation of the proposed model.